An efficiently tuned d-orbital occupation of IrO2 by doping with Cu for enhancing the oxygen evolution reaction activity1. Issue 8 (14th August 2015) - Sun, Wei; Song, Ya; Gong, Xue-Qing; Cao, Li-mei; Yang, Ji
<x xml:space="preserve">Abstract</x> Tuning Ir d-orbital occupation via doping Cu into the IrO2 lattice to prepare a highly efficient oxygen evolution reaction catalyst, Cu0.3Ir0.7Oδ.